2012
DOI: 10.1377/hlthaff.2012.0517
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies At Denver Health: ‘Patient Dumping’ In The Emergency Department Despite EMTALA, The Law That Banned It

Abstract: The Emergency Medical Treatment and Labor Act was enacted in 1986 to prevent hospitals from turning away patients with emergency medical conditions, often because they were uninsured--a practice commonly known as "patient dumping." Twenty-five years later, Denver Health--a large, urban, safety-net hospital--continues to experience instances in which people with emergency conditions, many of whom are uninsured, end up in the safety-net setting after having been denied care or receiving incomplete care elsewhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 1 publication
(1 reference statement)
1
25
0
Order By: Relevance
“…For example, a post-EMTALA study by Kao et al found evidence of increasing efforts by community hospital emergency departments to transfer uninsured patients to Stanford University Hospital between 2001-2006; interestingly, this study focused on transfer “requests” rather than completed transfers [22]. A post-EMTALA study published in Health Affairs provided a series of case studies where community-based hospitals and physicians provided incomplete evaluation and treatment of uninsured patients before transferring patients to a public hospital emergency department (Denver Health) for further treatment [23]; each case highlighted gaps in EMTALA regulations. Studies from the trauma literature in the post-EMTALA era have had conflicting findings but most have found that uninsured patents are significantly more likely to be transferred when compared to privately insured patients in the pre-hospital setting[10-13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a post-EMTALA study by Kao et al found evidence of increasing efforts by community hospital emergency departments to transfer uninsured patients to Stanford University Hospital between 2001-2006; interestingly, this study focused on transfer “requests” rather than completed transfers [22]. A post-EMTALA study published in Health Affairs provided a series of case studies where community-based hospitals and physicians provided incomplete evaluation and treatment of uninsured patients before transferring patients to a public hospital emergency department (Denver Health) for further treatment [23]; each case highlighted gaps in EMTALA regulations. Studies from the trauma literature in the post-EMTALA era have had conflicting findings but most have found that uninsured patents are significantly more likely to be transferred when compared to privately insured patients in the pre-hospital setting[10-13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the trauma literature in the post-EMTALA era have had conflicting findings but most have found that uninsured patents are significantly more likely to be transferred when compared to privately insured patients in the pre-hospital setting[10-13]. There has also been evidence of increased inter-hospital transfer of uninsured neonates compared to insured neonates [23]. We are unaware of any prior studies that have focused on the interplay between insurance coverage and inter-hospital transfer of adult patients who have already been admitted to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Other situations may appear suspicious but are not clear EMTALA violations. For example, some cases may reflect an EMTALA violation, an inaccurate diagnosis, or just a change in patient condition, such as a patient discharged from one hospital's ED for cholelithiasis (gallstones) and being admitted the next day by another hospital's ED for the more serious cholecystitis (gallbladder inflammation) . Although each individual case may not indicate a violation, when many such cases occur at a hospital, a pattern may arise, suggesting that at least some cases included violations.…”
Section: Overview Of Emtalamentioning
confidence: 99%
“…Studies of hospital behavior in the wake of PPS appeared to confirm this expectation. 18 A third factor was the continued stories of patient dumping, that is, of hospitals' refusal to provide any treatment in medical emergencies or else to send patients with confirmed medical emergencies away in unstable condition. Of particular note were stories of widespread dumping on public hospitals by other Medicare participating hospitals.…”
Section: Emtalamentioning
confidence: 99%